Analisis Penerapan Tarif Efektif Rata- Rata (TER) pada Pajak Penghasilan Pasal 21 dalam Peraturan Pemerintah Nomor 58 Tahun 2023 (Studi Kasus pada PT. Medikaloka Wonogiri) - Yayan Purnama Sari; Era Trianita Saputra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the implementation of Income Tax (PPh) Article 21 with Average Effective Rate (TER) at PT. Medikaloka Wonogiri. Using a qualitative approach, this study collected data through interviews and documents related to tax deductions, deposits, and reporting. The results of the study indicate that the implementation of this new scheme has been well received by employees, who did not protest the changes. Employees understand that there is no significant difference in the amount of tax to be paid compared to the previous scheme. In addition, the implementation of PPh Article 21 TER also contributes to increasing employee awareness and compliance with their tax obligations. This study concludes that tax reforms carried out by the government can have a positive impact on taxpayers, as well as increase state tax revenues. The advice given is for companies to continue to socialize tax policies and for the government to evaluate existing policies to create a more efficient and fair tax system.